2014
DOI: 10.1371/journal.pone.0105577
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Characterization of Purine Nucleoside Degrading Lactic Acid Bacteria Isolated from Chinese Sauerkraut and Evaluation of the Serum Uric Acid Lowering Effect in Hyperuricemic Rats

Abstract: Hyperuricemia is well known as the cause of gout. In recent years, it has also been recognized as a risk factor for arteriosclerosis, cerebrovascular and cardiovascular diseases, and nephropathy in diabetic patients. Foods high in purine compounds are more potent in exacerbating hyperuricemia. Therefore, the development of probiotics that efficiently degrade purine compounds is a promising potential therapy for the prevention of hyperuricemia. In this study, fifty-five lactic acid bacteria isolated from Chines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 37 publications
5
63
1
1
Order By: Relevance
“…Li et al showed the efficacy of the preventive treatment of hyperuricemic rats with probiotic strain DM9218-A. These results suggest that DM9218-A may be a promising candidate for the treatment of patients with hyperuricemia in conjunction with other therapies [ 46 ]. DM9218-A may also be effective in the prevention of hyperuricemia in the normal population.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al showed the efficacy of the preventive treatment of hyperuricemic rats with probiotic strain DM9218-A. These results suggest that DM9218-A may be a promising candidate for the treatment of patients with hyperuricemia in conjunction with other therapies [ 46 ]. DM9218-A may also be effective in the prevention of hyperuricemia in the normal population.…”
Section: Discussionmentioning
confidence: 99%
“…The lactic bacteria (LAB) strains isolated from fermented food or healthy human intestine were screened by MRS-cholesterol broth with the Ammonium ferric sulfate method [ 18 ]. The properties of selected candidate strains, including tolerance to acid, bile, pepsin and trypsin, cell adhesion ability were evaluated [ 19 ]. They were identified by 16S rDNA sequencing and the sequences were submitted to NCBI under the GenBank Accession No.…”
Section: Methodsmentioning
confidence: 99%
“…L. fermentum ONRIC b0185, L. fermentum ONRIC b0195 e L. pentosus ONRIC b0223, presented in cell, culture high nucleosidase activity converting nucleoside into purine bases [ 54 ]. The Lactobacillus DM9218 strain also acts on the purine nucleosides (inosine and guanosine) [ 55 , 56 ]. L. gasseri PA3 has demonstrated an ability to reduce purine in foods and beverages [ 57 , 58 , 61 ].…”
Section: Probiotics and Immunitymentioning
confidence: 99%
“…Probiotics can help maintain or restore the balance of the intestinal microbiome and, consequently, improve the immune system’s response against aggression to the human organism [ 50 ]. Among the mechanisms of probiotics that corroborate with intestinal and systemic health is the competition with pathogenic microorganisms for adhesion sites and nutritional sources, the secretion of antimicrobial peptides, the action of metabolites, nucleosidase activity, and even immunomodulation by signaling pathways of intestinal and immune cells [ 51 , 52 , 53 , 54 , 55 , 56 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation